The effects of economic policy uncertainty and large investment project on leverage - Sung Suk Kim; Rita Juliana; Liza Handoko (Asian Academy of Management Journal, 2023)
The dominant view on firms’ financial leverage suggests a stable, long-term leverage ratio, while previous studies recognise that factors like macroeconomic fluctuations and unanticipated financing needs can cause deviations from this target leverage. This study seeks to explore the joint effect of economic policy uncertainty (EPU) and large long-term investments on firms’ leverage decisions, specifically focusing on how these factors influence target leverage dynamics and financial flexibility. This study uses 2,865 listed firms in NYSE, NASDAQ, and AMEX from 1990 to 2019. The data is analysed through fixed effect panel regression model. The results show that EPU negatively affects firms’ leverage, which are reduced through joint effects with large investment for five years. This study also demonstrates firms’ financial flexibility motive to protect the debt capacity of large investments and enhance their capabilities.